1993
DOI: 10.2136/sssaj1993.03615995005700060018x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Desorption Quantity‐Intensity Relationships in Soils

Abstract: Phosphorus desorption quantity‐intensity (Q/I) relationships reveal information about the P release properties of a soil. This research was carried out to evaluate the P desorption characteristics of a group of soils of diverse properties and to compare several empirical models to describe P desorption Q/I curves. Samples of five soils (Typic Calciustoll, Udic Pellustert, Vertic Albaqualf, and Aridic Calciustoll surface soils, and Psammentic Paleudult subsoil) were enriched with five P concentrations (0, 25, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…When STP was regressed against adsorption and ancillary soil attributes (Table 4), R 2 values were generally lower than those for the fractions, although release into solution depends on desorbability of P as well as the level of labile P (Raven and Hossner 1993). All tests were associated positively with EPC for which a significant relationship with 0.01 M CaCl 2 P was reported previously (Reddy et al 1980).…”
Section: Multiple Regressions Of Stp Versus P Fractions P Adsorptionmentioning
confidence: 84%
“…When STP was regressed against adsorption and ancillary soil attributes (Table 4), R 2 values were generally lower than those for the fractions, although release into solution depends on desorbability of P as well as the level of labile P (Raven and Hossner 1993). All tests were associated positively with EPC for which a significant relationship with 0.01 M CaCl 2 P was reported previously (Reddy et al 1980).…”
Section: Multiple Regressions Of Stp Versus P Fractions P Adsorptionmentioning
confidence: 84%
“…However, there are a limited number of sorption sites in a kilogram of sediment matter, and the concentrations of these P forms must level out at some higher P saturation level (that was not covered by our material; i.e., the relationship actually has a shape of a Langmuirtype curve). By comparing the paper of Raven and Hossner (1993) to that of Barrow and Shaw (1977), it seems that at least some soils require excessive P additions to show a saturation of surface sorption sites. The former authors reported linear increase in AER-extractable P upon relatively modest P additions of up to 100 mg P kg -1 .…”
Section: Soil P Saturation and Runoff P Formsmentioning
confidence: 99%
“…(Barrow et al, 1998), o que justifica a menor adsorção do fosfato adicionado posteriormente (Raven & Hossner, 1993), como observado neste trabalho.…”
Section: Sistemas De Manejo De Solos E Os Valores De P Max E Kunclassified
“…Adições de fertilizantes fosfatados (maior P pre ) proporcionam maior cobertura dos sítios de sorção, saturando-os e diminuindo a variação da energia livre proporcionalmente ao recobrimento da superfície (Fox & Kamprath, 1970;Ryden et al, 1977;Barrow, 1978). Isso aumenta a dessortividade e diminui a relação sorvido/solução (Hartikainen, 1991;Raven & Hossner, 1993;Tolner & Füleky, 1995), o que pode causar erros de interpretação nas isotermas de adsorção.…”
Section: Introductionunclassified